2022
DOI: 10.1039/d2dt02217f
|View full text |Cite
|
Sign up to set email alerts
|

Novel oxaliplatin(iv) complexes conjugated with ligands bearing pendant 1,2-dithiolane/1,2-diselenolane/cyclopentyl motifs

Abstract: In this work, multiple biologically active α-lipoic acid (ALA) and its isologous 1,2-diselenolane (SeA) and cyclopentyl (CpA) analogues were investigated for their differences in redox potentials, cytotoxicity and ROS production....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…We routinely synthesize Ent-β-lactams from l -Ent-PEG 3 -N 3 6 and alkyne-modified β-lactams using Cu­(II) and sodium ascorbate (NaAsc) to generate Cu­(I) in situ . ,, Although this approach affords Ent-β-lactams in moderate to high yields (40–80%), , we did not employ it in the synthesis of l / d -EP due to the concern of potential Pt­(IV) reduction caused by NaAsc. , During attempts to optimize the CuAAC reaction described above that afforded l / d -EOP 3,4 , we reconsidered in situ reduction of Cu­(II) and evaluated the stability of oxPt­(IV)-alkyne 5 in the presence of NaAsc in water and DMF. We found that oxPt­(IV)-alkyne 5 remained stable throughout the 8 h incubation with NaAsc.…”
Section: Resultsmentioning
confidence: 99%
“…We routinely synthesize Ent-β-lactams from l -Ent-PEG 3 -N 3 6 and alkyne-modified β-lactams using Cu­(II) and sodium ascorbate (NaAsc) to generate Cu­(I) in situ . ,, Although this approach affords Ent-β-lactams in moderate to high yields (40–80%), , we did not employ it in the synthesis of l / d -EP due to the concern of potential Pt­(IV) reduction caused by NaAsc. , During attempts to optimize the CuAAC reaction described above that afforded l / d -EOP 3,4 , we reconsidered in situ reduction of Cu­(II) and evaluated the stability of oxPt­(IV)-alkyne 5 in the presence of NaAsc in water and DMF. We found that oxPt­(IV)-alkyne 5 remained stable throughout the 8 h incubation with NaAsc.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that increased lipophilicity within homologous series of Pt(IV) complexes may lead to enhanced cellular accumulation via passive diffusion [47]. Generally, conjugation with hydrophobic ligands leads to enhanced lipophilicity.…”
Section: Cellular Accumulationmentioning
confidence: 99%
“…6 Therefore, the reduction of Pt(IV) is a relevant process since the prodrug will be inactive if it is not easily reduced inside the cell and, on the other hand, if the reduction occurs before uptake into the cell, severe side effects will occur. 7 However, the rates of reduction depend on the ability of the ligands coordinated to Pt(IV) to facilitate the electron transfer from the reducing agent so that they do not necessarily correlate with the reduction potentials. 8,9 Several Pt(IV) compounds such as iproplatin, satraplatin, and tetraplatin, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%